Absence of Persistent Hepatitis E Virus Infection in Antibody-Deficient Patients Is Associated With Transfer of Antigen-Neutralizing Antibodies From Immunoglobulin Products. (18th August 2018) - Ankcorn, Mike; Moreira, Fernando; Ijaz, Samreen; Symes, Andrew; Buckland, Matthew S; Workman, Sarita; Warburton, Fiona; Tedder, Richard S; Lowe, David M
Abstract : A cohort of 245 antibody-deficient patients were tested for active hepatitis E virus (HEV) infection. No patient was viremic, but antigen-neutralizing anti–HEV immunoglobulin G was detected in patients sera and immunoglobulin products. Immunoglobulin replacement therapy may protect these patients from persistent HEV infection. Abstract: Background: Persistent hepatitis E virus (HEV) infection is described in a number of immunosuppressive conditions. We aimed to determine the risk of persistent HEV infection in patients with primary or secondary antibody deficiency. Methods: Two hundred forty-five antibody-deficient patients receiving regular immunoglobulin replacement therapy were tested for HEV RNA and anti–HEV immunoglobulin G (IgG). Immunoglobulin products and plasma specimens obtained from 9 antibody-deficient patients before and after intravenous immunoglobulin (IVIG) therapy, 5 recently treated patients with persistent HEV infection, and 5 healthy patients recovered from acute HEV infection were analyzed for anti–HEV IgG and for antibody reacting with HEV antigen. Results: No antibody-deficient patient had detectable plasma HEV RNA. Anti-HEV IgG was detected in 38.8% of patients. All 10 immunoglobulin products tested contained anti-HEV capable of neutralizing HEV antigen. Plasma samples collected following IVIG infusion therapy demonstrated a higher anti–HEV IgG level and neutralizing activity, compared with samples collected before IVIG therapy. Neutralizing activity was similar to that in healthy patients with recent acute HEV infection. Conclusion: The risk of persistent HEV infection in patients with antibody deficiency appears extremely low. This may be due to passive seroprotection afforded by the ubiquitous presence of anti-HEV in immunoglobulin replacement products.